Developing Teaching Materials with the ADI Model Assisted by Canva to Improve Procedural Text Writing Skills and Self-Confidence - Syafitri, Adiarni Decintya; Sobari, Teti; Minarti, Eva Dwi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
This study aimed to comprehensively examine the development process, feasibility, effectiveness, and implementation constraints of teaching materials based on the Argument-Driven Inquiry (ADI) model assisted by Canva in improving students’ procedural text writing skills and self-confidence. This research employed a Research and Development (R&D) method with the stages of needs analysis, design, product development, expert validation, product revision, limited trial, extensive trial, and final product. The results indicated that the development process was conducted in a structured and systematic manner in accordance with the R&D stages. The feasibility of the developed product was categorized as very feasible, as reflected by the average feasibility percentages of 97.07% for teaching materials, 96.19% for student worksheets, 94.67% for learning media, and 96.83% for lesson plans. Effectiveness testing showed a significant improvement in students’ procedural text writing skills, indicated by an increase in the mean score from 59.20 in the pretest to 76.85 in the posttest, with an N-Gain value of 0.41 in the moderate category. In addition, students’ self-confidence increased significantly from 49.64% in the fair category to 84.22% in the very good category. Implementation constraints included students’ need to adapt to the argument construction stage and the necessity for optimal time management by teachers. Overall, the Canva-assisted ADI teaching materials were proven to be feasible, effective, and have strong potential as an innovative alternative for teaching procedural text writing in elementary schools.